AREN: antara Kearifan Lokal dan Persaingan Global (Studi Ekofeminisme terhadap Perempuan di Alam Desa Campoan, Kecamatan Mlandingan, Kabupaten Situbondo) - Tia Oktaviani Safitri; Evi Resti Dianita (LP2M UIN Kiai Haji Achmad Siddiq Jember, 2021)
Palm sugar is a local product that is in demand in the global market. In Indonesia, the palm sugar industry is mostly done by the cold hands of women, especially in the villages. This fact is one of the clear evidence that dual role and emancipation have actually been formed naturally along with the awareness that women must participate in helping the economy of their families. This also happened in Campoan Village, where the palm sugar was found as home industry, which was directed by women. This fact showed us how a rural community unconsciously became the epicenter of feminism movement. This paper will discuss how the dual role of women in Campoan Village as the processors of palm sugar whose daily activities are close to nature and contribute to maintain environmental quality and nature sustainability. Exploration of the role of women in the context of rural development is an exotic thing to study. This is what makes this topic worthy of research.